Occurrence of threatened , endemic, and economic seed plants in selected mountains in Mindanao, Philippines - Lumista, Hannah P.; Dela Cruz, Reggie Y.; Acma, Florfe M.; Amoroso, Victor B. (2016)
Philippines is one of the biodiversity hotspots of the world, being home to most of the endangered species. It is important to give utmost attention to these plant taxa considered threatened, endemic, and economically important. The primary concern of this study to provide data on the occurrence and distribution of the threatened seed plants in Mindanao. Determination of these seed plants was based mainly on existing literature. Likewise, field observations were done in selected mountains in Mindanao to validate the occurrence and conservation status of these plants listed in the Philippine database. A total of 190 species of threatened seed plants were reported from Mindanao comprising 180 angiosperm species and ten gymnosperm species. More than half (133 species) of these threatened plants are endemic to the Philippines; 46 are placed in the critically endangered category, 69 endangered and 67 vulnerable. The families Orchidaceae and Dipterocarpaceae contained the highest number of threatened species. The family Melastomataceae is distinctly noted to have species which are all endangered and endemic to the country. The highest occurrence of threatened seed plants was observed in Mt. Malindang, Misamis Occidental. It is concluded that Mindanao houses some threatened, endemic, and economic seed plants.
Keywords: Mindanao studies; Endangered plants; Endemic plants